Enhancing organizational commitment among academic librarians: career development indicators as facilitating conditions (2024)
Librarians’ commitment is crucial for the success of any library. However, this subject has become a concern to library management as it dominates recent library literature. Hence, this study examined the effects of career development indicators on the organizational commitment of librarians in university libraries in Southern Nigeria. Survey research design was used for the study. The population comprised 556 professional librarians from university libraries in Southern Nigeria. The total enumeration sampling technique was used and the questionnaire method was employed for data collection. A returned rate of 94.2% (n¼524) was obtained. Data analysis was done using multiple regression analyses. Findings revealed that career development indicators had both significance and insignificance influence on the dimensions of organizational commitment of librarians in Southern Nigeria. Consequently, the study concluded that investing in career development indicators like mentoring and training will help to boost the organizational commitment of librarians, ultimately leading to increased productivity.